How Disturbed Sleep May Be a Risk Factor for Adverse Pregnancy Outcomes A Hypothesis - Okun, Michele L. (2009)
Adverse pregnancy outcomes associated with significant maternal and infant morbidity are on the rise in Western society despite advances of medical technology. Current risk factors are insufficient to identify women at greatest risk of developing an adverse outcome. An attempt to identify novel contributors to increased risk is warranted. Sleep disturbances are frequent during pregnancy, yet are often dismissed as irrelevant. Emerging evidence indicates that sleep disturbances are associated with poor health outcomes, including cardiovascular disease. Disturbed sleep is also linked with an increased inflammatory response. Increased inflammation is proposed as a key biological pathway through which chronic disease and adverse pregnancy outcomes develop. In this paper, we propose a model and a testable hypothesis of how disturbed sleep in the first 20 weeks of pregnancy could contribute to adverse pregnancy outcomes such as preeclampsia, intrauterine growth restriction, and preterm birth via increased inflammation. TARGET AUDIENCE: Obstetricians & Gynecologists, Family Physicians LEANING OBJECTIVES: After completion of this article, the reader should be able to outline data linking sleep disturbances with an increased risk of some systemic disorders, recall characteristics of pregnancy complications which support the hypothesis that sleep disturbances may be related to these pregnancy outcomes, and summarize the likelihood and types of sleep disturbances that are common in pregnant women.